Participatory Epidemiology of ethno-veterinary practices Fulani pastoralists used to manage contagious bovine pleuropneumonia and other cattle ailments in Niger State, Nigeria (2015)
Ethnoveterinary practices are locally available and affordable to Fulani pastoralists in Niger State, Nigeria, to whom conventional veterinary services are often not readily available and are relatively expensive. This study was designed to identify and document medicinal plant and nonplant materials used by this group in the management of cattle diseases. Participatory rural appraisal tools of checklist, semistructured interview, probing, transect, and triangulations were used to assess Fulani pastoralists existing knowledge on traditional veterinary practices in nine pastoral communities spread across the state. Fifty medicinal materials and seven traditional preventive practices are in use against CBPP and other cattle disease conditions. Of these, 38 (76.0%) are medicinal plants and 12 (24.0%) are nonplant materials (edible earth materials and minerals). Family Fabaceae was most commonly mentioned while leaves were the most common parts used. Most of these materials are administered by drenching with few others mixed with feed. Proportions of plant parts used include leaves (47.4%), barks (31.6%), roots (10.6%), and 2.6% of each of rhizomes, fruits, seeds, and whole plants. Of recently used ingredients are kerosene and spent engine oil. Further research into the active ingredients of ethnoveterinary materials and dosages is necessary to guide their usage.